Yes Day! - Rosenthal, Amy Krouse; Lichtenheld, Tom (New York : Scholastic, 2009)
A little boy gets everything he asks for on Yes Day, a special day that only comes once a year.
D
b
b
Keywords: Wishes -- Fiction; Day -- Fiction